Geodynamic Characteristics in the Southwest Margin of South China Sea - Yao, Yongjian; Zhang, Jian; Dong, Miao; Zhu, Rongwei; Xu, Zhiying; Yang, Xiaodong; Liu, Hailing (Frontiers in Earth Science, 2022)
The strike-slip fault zone in the southwestern margin of South China Sea (SCS) is located on the transition zone between the Eastern shelf of Vietnam and the western continental slope of SCS. It is an important sea-land tectonic boundary. By using submarine heat flow data, seismic shear wave tomography model, and gravity potential field data, this paper calculated and analyzed the distribution characteristics of submarine heat flow in the south of the western margin of SCS, the thermal-rheological structure of the crust and mantle, the temperature-viscosity characteristics of the upper mantle vs. low-velocity layer, the tangential stress field of the rheological boundary layer at the lithosphere base, and the convective velocity structure of the mantle asthenosphere. The results showed that the deep geothermal activity in the south of the western margin of SCS is intense, and the high heat flow area of the mantle with Qm/Qs>70% is distributed in an NNE-trending strip. Moreover, both east and west sides of the strike-slip fault zone in the western margin of SCS corresponds to two low-value areas with a viscosity coefficient of 10211022Pas at Moho depth, and beneath Nansha Block are hard and cold blocks with a viscosity coefficient of 10241025Pas. The northward and eastward shear stress components N and E of the rheological boundary layer at the base of the lithosphere mantle decrease with depth. At 65km depth, both N and E are greater than 5.5108N/m2. At 100km depth, both N and E are less than 1108N/m2. The fitting calculations based on the seismic shear wave model of the upper mantle and the gravimetric geoid model indicated that the depth of 120-250km is the vs. low-velocity layer, and the average temperature of the mantle at 180km depth can reach 1300°C. Moreover, the average effective viscosity coefficient is close to 1018Pas，which meets the temperature and viscosity conditions for partial melting or convective migration of mantle material. The mantle convection calculation results showed that the average flow rate is 8.5cm/a at 200km depth and 2.2cm/a at 400km depth.